THE RELATIONSHIP BETWEEN RELIGION AND CULTURE BASED ON PUBLICATIONS: A BIBLIOMETRIC STUDY - Imam Pribadi (Jurnal Scientia, 2022)
The importance of scientific journals in publishing research findings is essential to the advancement of science. one of which involves using library research, specifically through bibliometric analysis, is the process of identifying and determining research phenomena, trends, and innovations. This analysis allows researchers to acquire information from numerous scientific papers that have been published. The aim of this study is to evaluate the strength of the connection between religion and culture using academic journal articles. The research approach in this study makes use of bibliometric analysis by processing Google Scholar-sourced research data with the VosViewer and Harzing or Perish programs. The results of this study provide information that of the 200 samples observed, there are 163 samples that are relevant to the topic of research on religious and cultural relations during the 2010-2023 period. The results of the analysis found that research related to religion and culture is very much carried out but is still focused on Islam as the object of research. This is because Islam is the majority religion in Indonesia so that future researchers can use other religious object approaches to get different results. Keywords: Religion, Culture, Google Scholar, VosViewer and Harzing or Perish.